Defending Indonesian Sovereignty through Mass Media: Radio Rimba Raya in the Revolutionary War - Habibi Muttaqin; Sabil Mokodenseho; Febby Widjayanto (IHiS (Indonesian Historical Studies), 2022)
Radio as a medium of information plays an important role in the history of Indonesia's struggle. This study was conducted because of the previous studies on the movement to defend Indonesia's independence, only a few uses radio as a means of struggle. Radio Rimba Raya (RRR), which was established in Aceh. The aim is to analyze the role of RRR in defending Indonesian Independence, especially during the Second Dutch Military Aggression in 1948 and the General Offensive on March 1, 1949. Using the historical method, this study found that RRR became an important medium for nationalists to communicate orders and information, as well as providing an opportunity for Indonesia to thwart propaganda and dismiss Dutch provocations. Due to the importance of RRR in Indonesia's struggle, it can be concluded that one of the media for Indonesia's struggle and success against the Dutch was RRR with its messages that crossed the vast expanse of the contested area. The messages of struggle that were broadcast through the RRR were an important part of Indonesia's political strategy, both in dismissing Dutch propaganda and provocations and in guarding the agendas of Dutch-Indonesian diplomacy so that they were known to the public at home and abroad.